The Influence of Digital Marketing on Purchasing Decisions at Maliha Beaute Karawang - Fitriyan, Silvi; Hendriyani, Rina Maria (Journal of Economics Education and Entrepreneurship, 2024)
This study aimed to determine how much digital marketing influences purchasing decisions at Maliha Beaute Karawang. The research method is descriptive quantitative. One hundred eighty-four research respondents were clients of Maliha Beaute Karawang—data collection techniques through questionnaires. The collected data were analyzed using descriptive analysis and quantitative analysis of multiple linear regression. The study results show that digital marketing positively and significantly affects purchasing decisions. Then simultaneously shows that digital marketing positively and significantly affects purchasing decisions because the coefficient of determination is variable digital marketing on purchasing decisions of 0.518 or 51.8%, 51.8% of the purchase decision is influenced by digital marketing. At the same time, other variables outside of this study influence the remaining 48.2%.